Answer:
c, summing up. not the others
Answer:
Hello there!
Its C!
Step-by-step explanation:
It C because the others don't make as much sense as C! you could go try to see for yourself!
x+10=114
114-10=x
x=104
answer: n + 10 = 114 (n = 104 if this is needed)
work:
let's analyze the equation.
a number increased by 10 is 114
let's use n to represent this number.
a number increased by 10 is 114
let's add 10 to our number, n + 10
a number increased by 10 is 114
so, our equation equals 114. n + 10 = 114.
to find n, just subtract 10 from 114.
114 - 10 = 104
so, that completes and solves your equation, hope this helps and have a great day!
Do not include units (bracelets) in your answer.
Answer:
Mai can make 7 bracelets. (The answer to the question is 7)
Step-by-step explanation:
We know that each bracelet is made from 24.3 centimeters of string. We need to find out how many bracelets can be made from 170.1 centimeters.
To solve this equation, we need to divide 170.1 by 24.3.
170.1 ÷ 24.3 = 7
Therefore, Mai can make 7 bracelets. (The answer to the question is 7)
Hope this helps! :D
(a) What is the rate of change for each function? Show your work.
(b) Which function has the greater rate of change?
can you help me do these things
Answer:
The rate of change of first function is -2.
The rate of change of second function is 4.
Function 2 has greater rate of change.
Step-by-step explanation:
If a line passes through two points and , then the formula for rate of change is
From the table and graph consider any two points to find the rate of change of each function.
From the table, let as consider two point (-1,3) and (-2,5). The rate of change of first function is
The rate of change of first function is -2.
From the graph, let as consider two point (-1,0) and (0,4). The rate of change of second function is
The rate of change of second function is 4.
Since -2<4, therefore function 2 has greater rate of change.
Answer:
(x - 1)(x - 3)(x + 2).
Step-by-step explanation:
f(1) = 1^3 - 2(1)^2 - 5(1) + 6
= 1 - 2 - 5 + 6
= 0
so one factor is (x - 1) (by the Factor Theorem).
Divide f(x) by x - 1 we get:
x- 1) x^3 - 2x^2 - 5x + 6 ( x^2 - x - 6 <------ answer
x^3 - x^2
-x^2 - 5x
-x^2 + x
-6x + 6
-6x + 6
= x^2 - x - 6
= (x - 3)(x + 2).
x =
DONE
Answer:
x =4
Step-by-step explanation:
2 ln x = 4 ln 2
Divide each side by 2
2/2 In x = 4/2 In 2
ln x = 2 ln 2
Remember that a ln b = ln b^a
ln x = ln 2^2
ln x = ln 4
We are taking the natural log on both sides so , what we are taking the natural log of must be the same
x =4
Answer:
4
Step-by-step explanation:
Use the property of logarithms . (The number in front of ln becomes an exponent--or vice versa!)
Using that property on both sides, you get
But that means
Notice that is not a solution because is undefined. Negative numbers do not have logarithms. The domain of is the set of positive numbers.